Mining and validation of novel genotyping-by-sequencing (GBS)-based simple sequence repeats (SSRs) and their application for the estimation of the genetic diversity and population structure of coconuts (Cocos nucifera L.) in Thailand - Riangwong, Kanamon (Hortic Res, 2020)
Coconut (Cocos nucifera L.) is an important economic crop in tropical countries. However, the lack of a complete reference genome and the limitations of usable DNA markers hinder genomic studies and the molecular breeding of coconut. Here, we present the results of simple sequence repeat (SSR) mining from a high-throughput genotyping-by-sequencing (GBS) study of a collection of 38 coconut accessions. A total of 22,748 SSRs with di-, tri-, tetra-, penta- and hexanucleotide repeats of five or more were identified, 2451 of which were defined as polymorphic loci based on locus clustering in 38 coconut accessions, and 315 loci were suitable for the development of SSR markers. One hundred loci were selected, and primer pairs for each SSR locus were designed and validated in 40 coconut accessions. The analysis of 74 polymorphic markers identified between 2 and 9 alleles per locus, with an average of 3.01 alleles. The assessment of the genetic diversity and genetic relationships among the 40 coconut varieties based on the analysis of population structure, principal coordinate analysis (PCoA), and phylogenetic tree analysis using the 74 polymorphic SSR markers revealed three main groups of coconuts in Thailand. The identified SSR loci and SSR markers developed in this study will be useful for the study of coconut diversity and molecular breeding. The SSR mining approach used in this study could be applied to other plant species with a complex genome regardless of the availability of reference genome.